A comprehensive assessment of different wall boundary conditions on the simulation of bubbling fluidized beds. (February 2018) - Haghgoo, Mohammad Reza; Bergstrom, Donald J.; Spiteri, Raymond J.
Highlights: Three different particle-wall boundary conditions are examined to assess their ability to predict the dynamics of a dense gas-particle flow. The predicted dominant mixing regions inside the bed are identified and visualized in order to quantitatively describe the bed performance. The more energetic bubbles result in a lower level of granular temperature, a less-expanded bed, and more extensive mixing regions inside the bed. Some specific features of the predicted flows differ in a systematic way that can be tracked to the effect of wall boundary condition on the bubble behavior. Abstract: There are different particle-wall boundary conditions available in the literature to account for the particle slip velocity and the granular energy flux at the wall. However, it is not yet clear how these different wall boundary conditions affect the simulated flow behavior, nor is it clear which are the most realistic. To this end, three different particle-wall boundary conditions are examined to assess their ability to predict the dynamics of a dense gas-particle flow inside a three-dimensional bubbling bed, using the two-fluid model. To understand how the wall models affect structural features of the flow, a quantitative analysis is performed on some important aspects of the mechanics of bubbling beds that have received relatively little attention in the literature. Accordingly, the effect of each wall model on the velocity field, three-dimensional bubble statistics, gas-pressure fluctuations, and particle resolved-scale Reynolds stress are investigated. Also, the predicted dominant mixing regions inside the bed are identified and visualized in order to quantitatively describe the bed performance. It is found that the more energetic bubbles result in a lower level of granular temperature, a less-expanded bed, and more extensive mixing regions inside the bed. It is also observed that, in the case of bubbling beds, the mixing caused by the Reynolds normal stress is much stronger than that caused by the Reynolds shear stress. Overall, the flows predicted by the three wall models are structurally similar. However, some specific features can differ in a systematic way that can be tracked to the effect of wall boundary condition on the bubble behavior. The numerical results are validated against published experimental data and demonstrate the significant role of the particle-wall boundary condition.